Meta Analysis: Impact of Just in Time Implementation on Cost Efficiency and Profit - Urohman, Taufiq; Suryana, Alvian Jihad; Pandin, Maria Yovita R. (MultiTech Publisher, 2023)
Excessive inventory results in losses for the industry due to capital being held back, increased storage costs, incurring tax and inventory insurance costs, the risk of falling prices and quality, and giving rise to the potential for damage and theft. Inventory shortages can also cause losses because they can disrupt the production process. This research identified and analyzed 20 journals related to the implementation and impact of just in time implementation. Implementing just in time can reduce inventory costs, increase time efficiency and production costs so that producers can focus more on quality and increase company profits. The implementation of just in time is accompanied by an increase in other higher costs, this can be caused by constraints in the supply chain and the risk of uncertain demand.